The effectiveness of problem-based learning approach in science subject - Nurul Hazwani Shamsudin; Izzati Azmi; Shahrizal Idzuan Wahab Abdul Rahman; Nik Hanis Zuraihan Rahimi; Yuvenitha A/P Subramaniam (International Journal of Evaluation and Research in Education (IJERE), 2026)
The study was conducted to investigate the effectiveness of problem-based learning (PBL) on the achievements of Form one science students in Klang. Malaysia’s low ranking in scientific knowledge, as highlighted by the Programme for International Student Assessment (PISA), underscores the need for innovative teaching methods. Therefore, this study investigates the impact of PBL intervention on science subjects among 60 Form one students consisting of 30 treatment group and 30 control group students. The research instruments used were pre-test and post-test designed by the researcher. The pre-test was conducted using both treatment and control group students. The treatment group was exposed to PBL intervention for eight weeks before post-tests were given to both groups. Data was analyzed by using the independent t-test and paired t-test for pre-test and post-test. The research findings showed that the treatment group demonstrated significantly higher post-test scores than the control group. The findings suggest that the PBL approach positively impacts students’ learning achievements. Therefore, the study supports the adoption of PBL to enhance science education among Form one students.